2018
DOI: 10.1039/c8tc00820e
|View full text |Cite
|
Sign up to set email alerts
|

Resonant phonon scattering in semiconductors

Abstract: The origins of the dramatic effect of some dopants on the thermal conductivity of semiconductors are studied. By analyzing the cases of B-doped 3C-SiC, B-doped diamond, N-doped diamond and a simple linear chain model, small symmetry breaking structural distortions and a high density of states are identified as the key ingredients in resonant phonon scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…It is important to note how the present case is very different from our previous work on SiC. 34,35 In the present work, we observe a significant contribution of both EPS and PDPS to κ of a highly-doped system; whereas in our previous work we observed that PDPS was sufficient on its own to correctly predict the κ of B-doped cubic SiC owing to the resonant phonon scattering that boron causes. 34,35 The resonant scattering was at least one to two orders of magnitude higher than that caused by other defects and resulted in a drastic reduction (approximately two orders of magnitude at room temperature) in the thermal conductivity even at relatively mod- est defect concentrations (≈ 10 20 cm −3 ).…”
Section: Resultscontrasting
confidence: 84%
“…It is important to note how the present case is very different from our previous work on SiC. 34,35 In the present work, we observe a significant contribution of both EPS and PDPS to κ of a highly-doped system; whereas in our previous work we observed that PDPS was sufficient on its own to correctly predict the κ of B-doped cubic SiC owing to the resonant phonon scattering that boron causes. 34,35 The resonant scattering was at least one to two orders of magnitude higher than that caused by other defects and resulted in a drastic reduction (approximately two orders of magnitude at room temperature) in the thermal conductivity even at relatively mod- est defect concentrations (≈ 10 20 cm −3 ).…”
Section: Resultscontrasting
confidence: 84%
“…In fact, a marked peak in the imaginary part of the trace of the scattering T matrix has been shown to be a straightforward way to identify the resonance scattering. 5,11 A very sharp peak also appears in the BB-DX case at about 5.9 rad ps −1 , whereas the anomalously high scattering rates of β-CCB-DX are mainly found around 8 rad/ps, close to where the trans- verse acoustic band of GaAs enters the edge of the Brillouin zone. 33 As can be seen by comparing Figs.…”
Section: Resultsmentioning
confidence: 96%
“…In a previous study, we posited that two or more close energy minima in the energy landscape are a necessary condition for having resonant phonon scattering since they create very flat-bottomed energy valleys. 11 Thus, we calculate the barriers to transitions between different configurations using the NEB method. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second-order FCs of systems with many atoms and/or low symmetry can be tedious to obtain by the direct approach. This applies in particular to the FCs of defect configurations, which are needed for example for computing the vibrational contribution to the free energy of defect formation 16 , analyzing the impact of defects on the thermal conductivity 18,38,39 or predicting the vibrational broadening of optical spectra 40,41 . In this section, we therefore analyze the extraction of second-order FCs for the vacancy in body-centered cubic (BCC) Ta as a prototypical case, using both the direct approach as implemented in PHONOPY 25 and the regression approach as implemented in HIPHIVE 15 .…”
Section: Second-order Fcs: Large Low-symmetry Systemsmentioning
confidence: 99%